ANALISIS IMPLEMENTASI UNDANG-UNDANG NOMOR 6 TAHUN 2014 DALAM MEWUJUDKAN AKUNTABILITAS PENGELOLAAN KEUANGAN DESA (Studi Kasus Pada Dua Desa di Kecamatan Toapaya Kabupaten Bintan) - Annisa Furqani Arigusti; Taufeni Taufik; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to analyze (1) How the implementation of village financial management in Toapaya Sub-district, Bintan Regency, starting from planning, implementation, administration, reporting, and financial accountability. (2) How to foster and supervise the management of village finances in Toapaya Subdistrict, Bintan Regency.The method used in this research is descriptive method with comparative qualitative analysis to six research variables, namely Planning, Implementation, Administration, Reporting, Accountability and Development and Supervision of Village Financial Management. This study compiles the implementation of village financial management conducted in Toapaya Village and South Toapaya Village and compares with Law No. 6 of 2014 and its supporting regulations such as Permendagri Number 113 of 2014 and Permendagri No. 114 of 2014. The result of the research shows that based on Law Number 6 Year 2014, the implementation of financial management of Toapaya and Toapaya Selatan villages is accountable, but technically there are still some obstacles such as delay in fund disbursement causing delays in reporting, and utilization of Village Finance System (SISKEUDES ) that has not been effective in Toapaya Village caused by the lack of village officials' ability to use the application, has not yet published its financial accountability in Toapaya Village. Therefore, more intensive coaching for Toapaya Village is needed in the utilization of existing SISKEUDES.Keywords: Accountability, Law Number 6 Year 2014, Permendagri 113 Year 2014, Permendagri 114 Year 2014, Village Financial Management